HERBICIDE TOLERANCE GENES DERIVED FROM BACTERIA - Y. Kaya; S. Marakli; N. Gozikirmizi; E. Mohamed; M.A. Javed; F. Huyop (Journal of Animal and Plant Sciences, 2013)
Nowadays, gene transformation methods play an important role in plant improvement. Herbicides are an integral part of modern day agriculture as they facilitate efficient crop management. Most of the herbicides target specific enzymes involved in metabolic pathways that are vital for plant growth and survival. In plant biotechnology applications, the use of herbicide tolerance genes have created new approaches with the obtained herbicide tolerant plants. This review describes herbicide tolerance; concerning of herbicide tolerant transgenic crops with the genes derived from bacteria.
Keywords: herbicide; herbicide resistant plant; herbicide tolerance genes; dehalogenases